Efek Ekstrak Buah Kelor (Moringa oleifera) Terhadap Penurunan Kadar Gula Darah Mencit (Mus musculus) - Pitriya, Ida Ayu; Rahman, Nurdin; Sabang, Sri Mulyani (Jurnal Akademika Kimia, 2017)
The plant could be potential as a traditional medicine, relatively safe, and inexpensive, that is of Moringa (moringa oleifera) fruit, which contains compounds those can lower blood sugar levels. The purpose of this study was to investigate the effect of Moringa fruit extracts on decreasing blood sugar levels of mice and to determine the most effective concentration of the extract. The separation method used was maceration. The animals test used were 15 male mice induced by EDTA. Mice were divided into 5 groups with different treatments. The first, the second, and the third treatments were given moringa extracts each with a concentration of 10, 20, and 40%. The fourth treatment was given glibenclamide suspension as a positive control, and the fifth treatment was given Na-CMC as a negative control. Data were analyzed using a statistical analysis of variance (ANOVA) test followed by Duncan test. The results showed that Moringa fruit extract lowered blood sugar levels of mice. The means decrease of blood sugar levels for each treatments were 49.67 mg/dL for the first, 58.33 mg/dL for the second, 70.33 mg/dL for the third, 66.67 mg/dL for the fourth, and 10.00 mg/dL for the fifth, . This study concluded that the Moringa fruit extract decreased blood sugar levels of mice with the most effective concentration of 10% and Î± = 0.05.